THE DEVELOPMENT OF MOLECULAR SPECIES TYPING SYSTEM FOR IXODES PERSULCATUS AND IXODES PAVLOVSKYI TICKS - S. E. Tkachiov; N. N. Livanova (Acta Biomedica Scientifica, 2012)
Determination of ticks species is very important for epidemiology and ecology investigations but in some cases the morphological study couldn't be carried out. In this work the PCR system based on species-specific primers to cytochrome oxidase subunit 1 (COI) gene sequence was developed for molecular species typing of Ixodes persulcatus and. Ixodes pavlovskyi ticks.